Potential of Biochar-Based Fertilizers for Increasing the Productivity of Okra in Gajuri, Dhading - Aavash Shrestha; Rijwan Sai; Manjul Devkota (Turkish Journal of Agriculture: Food Science and Technology)
Sustainable agricultural production depends on increasing crop productivity while preserving soil health and reducing environmental risk. The purpose of this study was to evaluate the potential of biochar (10 t ha-1) based organic and inorganic fertilizer for increasing okra productivity through a field experiment conducted in Gajuri, Dhading. A 130 m2 area was divided into six treatment groups, each with four replications, using a Randomized Complete Block Design. The following were the treatments: i) inorganic fertilizer (RF); ii) biochar plus inorganic fertilizer (BF); iii) biochar plus vermicompost (BVC); iv) biochar plus poultry manure (BPM); v) biochar (BC); vi) control; neither biochar nor fertilizer (CK). The recommended rates of urea, di-ammonium phosphate (DAP), and muriate of potash (MOP) were applied to the mineral NPK fertilizers in RF and BF. The rate whereby organic fertilizers were applied was 200 kg N ha-1. Plots treated with biochar and various fertilizer groups were compared in terms of growth and yield efficiency. The BVC treatment was found to exhibit poorer growth performance in terms of plant height, number of leaves, primary branches, and nodes compared to the combination of biochar and poultry manure. Fruit output rose by 170% over CK (7.13 mt ha-1) and by 53.26% over RF (12.58 mt ha-1) after BPM treatment (19.28 mt ha-1). While BF and RF did not significantly differ in terms of growth characteristics, BF outproduced RF by 29% and CK by 126.79% in terms of pod yield. BF and BPM offered greater financial rewards than alternative treatments.